2011
DOI: 10.1016/s0924-9338(11)72080-6
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles among post-myocardial infarction patients with depressive symptoms

Abstract: ObjectiveAlthough the adverse impact of post-myocardial infarction (MI) depressive symptoms on prognosis of heart disease has been found, the link between coping strategies and post-MI depressive symptoms has yet been unclear. The aim of this study was to determine the relationship between coping styles and post-MI depressive symptoms.MethodsIn a cross sectional study one hundred consecutive patients following MI admitted to the CCU wards of hospitals in Isfahan were selected in respect of inclusive and exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results showed that the highest and lowest scores of coping strategies pertained to distancing and confronting coping. In line with our findings, Bagherian et al stated that hemodialysis patients were more likely to use escape avoidance strategy than confronting coping (15). However, Ahmad and Al Nazly stated that patients undergoing hemodialysis obtained the highest score in the positive re-assessment strategy and that they had the lowest score in the decision-making strategy (18).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the highest and lowest scores of coping strategies pertained to distancing and confronting coping. In line with our findings, Bagherian et al stated that hemodialysis patients were more likely to use escape avoidance strategy than confronting coping (15). However, Ahmad and Al Nazly stated that patients undergoing hemodialysis obtained the highest score in the positive re-assessment strategy and that they had the lowest score in the decision-making strategy (18).…”
Section: Discussionsupporting
confidence: 90%
“…The most commonly used strategies were returning to God, active opposition, and suppression of activities (14). The study of Bagherian et al showed that patients were more likely to use less direct strategies and mainly used relieving and avoidant styles in dealing with stress, but healthy individuals in stress-related situations often used more direct coping strategies (15).…”
Section: Introductionmentioning
confidence: 99%